2002
DOI: 10.1515/ling.2002.010
|View full text |Cite
|
Sign up to set email alerts
|

On the diphthong/hiatus contrast in Spanish: some experimental results

Abstract: Some Spanish dialects have a lexical contrast between sequences in hiatus and diphthongs. Thus, whereas, for instance, dueto 'duet' admits a trisyllabic pronunciation with the sequence ue realized in hiatus [du.é.to], the word duelo 'sorrow' can only be pronounced as bisyllabic [dwé.lo]. Similarly, [pi.é] 'I chirped' contrasts with [pjé] 'foot' in this manner. The interest of this phenomenon lies in the fact that it represents a clear case of phonological contrasts between hiatus and diphthong or, in other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 4 publications
2
43
0
6
Order By: Relevance
“…(3). The predicted duration of D is 133 ms, while for H this is 181 ms, which is in line with the findings in Aguilar (1999) and in Hualde and Prieto (2002). The difference between the means is highly significant and class (i.e.…”
Section: Analysis Of Durationsupporting
confidence: 88%
See 3 more Smart Citations
“…(3). The predicted duration of D is 133 ms, while for H this is 181 ms, which is in line with the findings in Aguilar (1999) and in Hualde and Prieto (2002). The difference between the means is highly significant and class (i.e.…”
Section: Analysis Of Durationsupporting
confidence: 88%
“…More recently, analyzed the alignment of rising pitch accents in Spanish segmental sequences involving a similar gestural content but differing in syllabic structure, including the diphthongs and hiatuses investigated in the present study. In agreement with the syllabification patterns proposed by Hualde and Prieto (2002), it was found that rising pitch accents in /ia/ hiatuses were aligned with the second vowel of the sequence, while in diphthongs, the start of rising accents was aligned earlier, presumably at the onset of the syllable containing the diphthong. Since the onset of rising pitch accents in Spanish have been reported to be aligned with the beginning of lexically stressed syllables (Prieto, van Santen, & Hirschberg, 1995;Prieto & Torreira, 2007), this study concluded that the differences in f 0 alignment must be due to differences in syllabification of /ia/ vowel sequences (i.e.…”
Section: Case Studysupporting
confidence: 87%
See 2 more Smart Citations
“…For example, Hualde and Prieto (2002) established that the acoustic difference between Spanish diphthongs and hiatuses lies in the mean duration values of the two vocoids. Cabré and Prieto (2004) provide a broad empirical study of the present-day lexical distribution of the rising diphthong/hiatus alternations in Central Catalan and represent the results in the form of OTed tableaux.…”
Section: Haładewicz-grzelakmentioning
confidence: 99%